JEWELRY AND DESIGN, A MARRIAGE OF CONVENIENCE - Muñoz Mesa, Laura
Jewerly is a traditional activity in our country, taking into the account Colombia as a gold producer, it should be recognized because of its jewerly but it is not, and it is caused by the design. Colombian jewerly does not stand out internationally which has its beginning in the training. Fashion design apprentices show their ability to design jewerly but they do not know about technical aspects which are important. Jewerly complement the outfit making an integral style proposal. This statement has been demostrated by some designers like Coco Chanel, Silvia Tcherassi or Andrés Pajón. The Centro de Formación en Diseño, Confección y Moda has, as an advantage, both programs, it is a very good opportunity to improve the learning processes. The Centro has developed a synergy between design and jewerly apprentices, they will make a jewerly collection to show in a runway during the “Bucaramanga Diseña” event. The objective of that synergy was to direct the appropriateness of this kind of alliances through case analysis. Methodology: 1. To form an interdisciplinary group. 2. Studying the proposed topic. 3. Making and socializing the sketches and proposals. 4. Production. 5. Divulgation. 6. Results assessment. Each part is documented. As a result of the process true jewels were gotten, there were a knowledge interchange and as a conclusion, the interdisciplinary work is rewarding, favoring the personal and professional growing, getting disruptive and stunning results which break the habits and capture the attention.